Left atrial strain, intervendor variability, and atrial fibrillation recurrence after catheter ablation: A systematic review and meta-analysis - Dimitrios Mouselimis; Anastasios S. Tsarouchas; Eftstathios D. Pagourelias; Constantinos Bakogiannis; Efstratios K. Theofilogiannakos; Charalampos Loutradis; Nikolaos Fragakis; Vassilios P. Vassilikos; Christodoulos E. Papadopoulos (Hellenic Journal of Cardiology, 2020)
The aim of this systematic review and meta-analysis is to investigate the capacity of preinterventional left atrial strain (LAS) to predict AF recurrence (AFR) after catheter ablation by using all relative published data. Intervendor variability regarding different ultrasound stations and strain analysis software suites was taken into consideration. The research was performed according to PRISMA guidelines. The Cochrane database, MEDLINE, and EMBASE were searched for studies assessing echocardiography LAS prior to catheter ablation of AF cases. The systematic research yielded 10 studies (2 retrospective and 8 prospective, 880 patients in total). LAS differed significantly between the patients with AFR and those with no AF recurrence (nAFR) during the follow-up period (LASAFR: 17.5 ± 8.7% vs. LASnAFR: 24.1 ± 9.5%, p < 0.00001). A pooled cutoff value of 21.9% for LAS was extracted for the prediction of ablation success. Regarding intervendor variability, subgroup analyses were able to be performed for studies using GE and TomTec software. The difference in LASAFR and LASnAFR remained significant (p < 0.00001 and p < 0.0001 for TomTec and GE, respectively), while significant intervendor difference in absolute strain values was also detected (p < 0.0001 for both AFR and nAFR groups). LAS prior to catheter ablation is consistently lower in patients who experience AF recurrence. Its incorporation in clinical practice would assist physicians detect patients who require closer follow-up. Intervendor variability appears to be considerable and steps must be taken to document it thoroughly and mitigate it if possible.